2016
DOI: 10.1007/s00134-016-4331-6
|View full text |Cite
|
Sign up to set email alerts
|

Personalized medicine for ARDS: the 2035 research agenda

Abstract: Survival from ARDS has increased substantially in the last twenty years as a result of key advances in lung-protective ventilation and resuscitation. Similarly, clinical practice improvements have contributed to an impressive decline in nosocomial ARDS incidence. Personalizing mechanical ventilation for further lung protection is a top research priority for the years ahead. However, the ARDS research agenda must be broader in scope. The clinical syndrome of ARDS includes a heterogeneous assemblage of pathophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 77 publications
(99 reference statements)
0
48
0
1
Order By: Relevance
“…
Since 1967, when first described, ARDS has been widely recognized as a major health problem worldwide, carrying a high morbidity and mortality [1][2][3]. This focus editorial summarizes recent advances about the incidence, pathophysiology, right ventricular dysfunction, and mortality of ARDS.

Despite the attempt to homogenize its definition following the publication of the Berlin criteria, there is still a high heterogeneity in the epidemiology of ARDS across the world [3].

…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
Since 1967, when first described, ARDS has been widely recognized as a major health problem worldwide, carrying a high morbidity and mortality [1][2][3]. This focus editorial summarizes recent advances about the incidence, pathophysiology, right ventricular dysfunction, and mortality of ARDS.

Despite the attempt to homogenize its definition following the publication of the Berlin criteria, there is still a high heterogeneity in the epidemiology of ARDS across the world [3].

…”
mentioning
confidence: 99%
“…Since 1967, when first described, ARDS has been widely recognized as a major health problem worldwide, carrying a high morbidity and mortality [1][2][3]. This focus editorial summarizes recent advances about the incidence, pathophysiology, right ventricular dysfunction, and mortality of ARDS.…”
mentioning
confidence: 99%
“…Based on these general recommendations clinicians should individualize the therapy for their patients, especially regarding the presented conditional recommendations. Personalizing mechanical ventilation to patient-specific physiology to further enhance lung protection will be a top research priority for the years ahead, as stated by the ARDSne(x)t investigators (25). Profound understanding of the heterogeneous pathophysiological processes leading to the development of ARDS is needed to tailor ventilatory and other therapeutic strategies to the individual patient.…”
mentioning
confidence: 99%
“…Profound understanding of the heterogeneous pathophysiological processes leading to the development of ARDS is needed to tailor ventilatory and other therapeutic strategies to the individual patient. The next 20 years of ARDS research require that we ask not just whether novel preventive or therapeutic interventions work but also in whom (25).…”
mentioning
confidence: 99%
“…It is concluded that the combination of ECCO 2 -R with renal replacement therapy allows a safe and adequate blood 'purification' of renal-and pulmonary-associated substances together while enhancing lung protective ventilation in critically ill patients. The trend towards a 'personalised medicine' has reached intensive care medicine and the management of ARDS patients should be revisited accordingly [5]. ECCO 2 -R could become an important part of such a project in a 'balanced' portfolio of extracorporeal lung support.…”
mentioning
confidence: 99%